A promised presence : a systematic theological inquiry into the theodicy question in the thought of Jürgen Moltmann and Paul S. Fiddes - Stander, Reinhardt (Stellenbosch : Stellenbosch University, 2018)
Thesis (MTh)--Stellenbosch University, 2018.